Sexual Consent Paradigm In The Framework Of Indonesian Legal: A Comparative Islamic Perspective - Muhammad Taufiq (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
This research aims to analyze the sexual consent paradigm in the Sexual Violence Crime Law and compare it with the principles of Islamic law. The focus of the research is to understand the extent to which the two paradigms are aligned or different in terms of protecting individual rights against sexual violence. This research uses qualitative methods with normative and comparative approaches. Analysis was carried out on the text of the TPKS Law and sources of Islamic law, such as the Al-Qur'an, hadith, as well as the opinions of ulama regarding sexual consent. Data was collected through literature studies and legal documents. Research findings show that the TPKS Law emphasizes the importance of free, conscious and non-coerced consent in sexual relations, regardless of marital status. In contrast, Islamic law provides a stricter framework regarding legal sexual relations only within the context of marriage. While both recognize the importance of consent, deep differences emerge over the limits and scope of legitimate relationships according to religion. The sexual consent paradigm in the TPKS Law and the principles of Islamic law have similarities in the aim of protecting individuals from sexual violence, but there are significant differences in their application. The TPKS Law adopts a more universal approach, while Islamic law places more emphasis on legitimate relationships within marriage. This research recommends the need to integrate religious values ​​in national legal policies to achieve more holistic justice.